2019
DOI: 10.1007/s10549-019-05216-w
|View full text |Cite
|
Sign up to set email alerts
|

Utility of ankyrin 3 as a prognostic marker in androgen-receptor-positive breast cancer

Abstract: Purpose. Androgen receptor (AR) and AR signaling pathways are thought to play a role in breast cancer (BC) and are potentially related to treatment responses and outcomes. Ankyrin 3 (ANK3) is associated with AR stability in cancer cells. In the present study, we investigated the clinicopathological utility of ANK3 expression with emphasis on AR and its associated signalling pathway at transcriptomic and proteomic phases. Patients and Methods. The Molecular Taxonomy of Breast Cancer International Consortium (ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
1
11
1
Order By: Relevance
“…The specificity of the LCN2 antibody (LS-C405956; Lifespan Biosciences, Seattle, WA) (dilution: 1:500) was validated, and a specific band (70 kDa) was detected through western blotting of lysate obtained from the cell line HeLa (The American Type Culture Collection, Rockville, MD) (Supplementary Fig 1). Full-face tissue sections from patients with invasive breast cancer (n = 10) [24][25][26] were stained before tissue microarray (TMA) to assess the morphological characteristics of LCN2 expression and test the suitability of this method. TMA sections from the discovery and validation sets were IHC-stained to evaluate the expression of LCN2 protein.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The specificity of the LCN2 antibody (LS-C405956; Lifespan Biosciences, Seattle, WA) (dilution: 1:500) was validated, and a specific band (70 kDa) was detected through western blotting of lysate obtained from the cell line HeLa (The American Type Culture Collection, Rockville, MD) (Supplementary Fig 1). Full-face tissue sections from patients with invasive breast cancer (n = 10) [24][25][26] were stained before tissue microarray (TMA) to assess the morphological characteristics of LCN2 expression and test the suitability of this method. TMA sections from the discovery and validation sets were IHC-stained to evaluate the expression of LCN2 protein.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Somatic mutation of GATA3 is associated with clinicopathological features and expression of TCGA in breast cancer patients (30). FANCD2 (31), DAB1 (32) and ANK3 (33) are all supported by literature to be associated with breast cancer.…”
Section: Tmb Analysismentioning
confidence: 85%
“…Therefore, we speculate that ANK3 mutation might participate in subcellular localization in PTC cells. In contrast, Kurozumi ( 31 ) reported that breast cancer cells showed uniform ANK3 immunoreactivity primarily in the cytoplasm. These results suggested that the different subcellular localization of ANK3 protein is associated with different cancer types.…”
Section: Discussionmentioning
confidence: 95%
“…Several recent studies have reported that ANK3 is strongly associated with bipolar disorder ( 29 , 30 ). Moreover, studies have demonstrated that ANK3 is associated with prostate cancer and breast cancer by regulating the stability of AR ( 31 , 32 ).…”
Section: Resultsmentioning
confidence: 99%